Isolated Loss of PMS2 Immunohistochemical Expression is Frequently Caused by Heterogenous MLH1 Promoter Hypermethylation in Lynch Syndrome Screening for Endometrial Cancer Patients. (June 2016) - Kato, Aya; Sato, Naoki; Sugawara, Tae; Takahashi, Kazue; Kito, Masahiko; Makino, Kenichi; Sato, Toshiharu; Shimizu, Dai; Shirasawa, Hiromistu; Miura, Hiroshi; Sato, Wataru; Kumazawa, Yukiyo; et al.
Abstract : Lynch syndrome (LS) is an autosomal-dominant inherited disorder mainly caused by a germline mutation in the DNA mismatch repair (MMR) genes ( MLH1, MSH2, MSH6, and PMS2 ) and is associated with increased risk for various cancers, particularly colorectal cancer and endometrial cancer (EC). Women with LS account for 2% to 6% of EC patients; it is clinically important to identify LS in such individuals for predicting and/or preventing additional LS-associated cancers. PMS2 germline mutation (PMS2-LS) is the rarest contribution to LS etiology among the 4 LS-associated MMR germline mutations, and its detection is complicated. Therefore, prudent screening for PMS2-LS is important as it leads to an efficient LS identification strategy. Immunohistochemistry is recommended as a screening method for LS in EC. Isolated loss of PMS2 (IL-PMS2) expression is caused not only by PMS2-LS but also by MLH1 germline mutation or MLH1 promoter hypermethylation (MLH-PHM). This study aimed to determine the association between MLH1-PHM and IL-PMS2 to avoid inappropriate genetic analysis. We performed MLH1 methylation analysis and MLH1/PMS2 germline mutation testing on the IL-PMS2 cases. By performing MMR-immunohistochemistry on 360 unselected ECs, we could select 8 (2.2%) cases as IL-PMS2. Heterogenous MLH1 staining and MLH1-PHM were detected in 4 of 8 (50%) IL-PMS2 tumors. Of the 5 IL-PMS2 patients who underwent genetic analysis, 1 had PMS2 germline mutation with normal MLH1 expression (without MLH1-PHM), and no MLH1 germline mutation was detected. We suggest that MLH1 promoter methylation analysis for IL-PMS2 EC should be performed to exclude sporadic cases before further PMS2 genetic testing.